South Asia Bible commentary - Wintle, Brian C. (Brian Charles), 1944- (Open Door Publications Pvt Ltd., Rajasthan, India., 2015)
"A one-volume commentary, written and edited by South Asian Biblical scholars on all the books of the Bible"--
Description based on print version record
Keywords: Bible -- Commentaries; Theology -- South Asia